Studi Kasus: Konsep Dasar Pendidikan Inklusi pada Jenjang PAUD di Kota Banjarmasin, Kalimantan Selatan - Muzdalifah, Fithrii; Rahmaniah, Nahdia Fitri (Jurnal Ilmiah Global Education, 2024)
The background of this study is the implementation of inclusive education in early childhood education (PAUD) in Banjarmasin, Indonesia. This research aims to assess the understanding and commitment of educators and parents towards inclusive education, as well as the strategies and challenges faced in accommodating various learning needs. The methodology used is a qualitative case study approach involving in-depth interviews with educators, parents and children with special needs, as well as participant observation in 3 inclusive PAUDs in Banjarmasin. The research results show that there is a strong commitment and understanding of the principles of inclusive education among educators and parents in Banjarmasin. Key findings include acceptance of children with diverse abilities and backgrounds, adapting curricula to meet individual needs, and developing collaboration between educators, parents, and the community. However, challenges such as lack of human resources, infrastructure, and societal stigma towards children with special needs have been identified. The implications show the need for increased budget allocations, comprehensive training for educators, infrastructure improvements, and community education to support inclusive education.